Gabapentin treatment in a patient with KCNQ2 developmental epileptic encephalopathy. (October 2020) - Soldovieri, Maria Virginia; Freri, Elena; Ambrosino, Paolo; Rivolta, Ilaria; Mosca, Ilaria; Binda, Anna; Murano, Carmen; Ragona, Francesca; Canafoglia, Laura; Vannicola, Chiara; Solazzi, Roberta; Granata, Tiziana; et al.
Graphical abstract: ABSTRACT: De novo variants in KCNQ2 encoding for Kv7.2 voltage-dependent neuronal potassium (K + ) channel subunits are associated with developmental epileptic encephalopathy (DEE). We herein describe the clinical and electroencephalographic (EEG) features of a child with early-onset DEE caused by the novel KCNQ2 p.G310S variant. In vitro experiments demonstrated that the mutation induces loss-of-function effects on the currents produced by channels incorporating mutant subunits; these effects were counteracted by the selective Kv7 opener retigabine and by gabapentin, a recently described Kv7 activator. Given these data, the patient started treatment with gabapentin, showing a rapid and sustained clinical and EEG improvement over the following months. Overall, these results suggest that gabapentin can be regarded as a precision therapy for DEEs due to KCNQ2 loss-of-function mutations.